Analysis on Perpetrator of Klithih In Special Region of Yogyakarta - Endro Rasetya Prasetyandoko; Yeni Widowaty (Faculty of Law, University of Mataram, 2021)
This crime often occurred and can directly be witnessed and committed publicly of Yogyakarta, this type of crime known as Klithih. Crimes committed by the offender emerge general reaction as this act may disturb public. It is not only harm a single victim but also multiple. This crime majorly offended by secondary senior high school teens. Aims of this research related to criminology study on Klithih offender in special region of Yogyakarta are to find out causing factors as well as to find out countermeasure efforts of the authorities on such a crime and enforcement concept on the crime in Yogyakarta. This research applied juridical-empirical legal research method namely applied procedure to overcome problems by researching secondary prior to analysing primary data that collecting from field research. The primary data collected from interviews with informants, meanwhile secondary data are collected from documentation, books, literatures and archives that related with research object. Data analysis is applying qualitative method that analysing normative (juridical) aspects under a descriptive-analysis manner. Research result indicates that (1) causing factors of Klithih crime in the special region of Yogyakarta are including revenge, circumstances, alcohol and the lack of education; (2) efforts taken by police to overcome Klithih crime in the special region of Yogyakarta namely penal and non-penal acts.